2016
DOI: 10.1016/j.ejvs.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective Intra-procedural AAA sac Embolization During EVAR Reduces the Rate of Type II Endoleak

Abstract: Selective intra-procedural AAA sac embolization in patients with p-MRF is safe and could be an effective method to reduce ELIIp. Further studies are mandatory to support these results at long-term follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 26 publications
2
55
0
Order By: Relevance
“…In 10 (47.6%) patients, considered at high risk of ELII due to the presence of the morphological risk factors cited before [ 16 ], a 45 cm long 5 F Terumo® Destination sheath was introduced over the wire, parallel to the contralateral limb and advanced under fluoroscopy to the AAA-sac. Once the endograft was completely deployed and the aneurysm excluded, Cook MReye coils (MReye Embolization Coil, IMWCE-38-16-45; Cook Medical, Limerick, Ireland),were advanced into the sac through 5 F sheath and intraoperative AAA-sac embolization was performed [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 10 (47.6%) patients, considered at high risk of ELII due to the presence of the morphological risk factors cited before [ 16 ], a 45 cm long 5 F Terumo® Destination sheath was introduced over the wire, parallel to the contralateral limb and advanced under fluoroscopy to the AAA-sac. Once the endograft was completely deployed and the aneurysm excluded, Cook MReye coils (MReye Embolization Coil, IMWCE-38-16-45; Cook Medical, Limerick, Ireland),were advanced into the sac through 5 F sheath and intraoperative AAA-sac embolization was performed [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients considered at high risk for persistent type II endoleak (ELII) according to their anatomical characteristics (≥6 efferent patent vessels from AAA-sac, volume of AAA-sac intraluminal thrombosis <40%) [ 16 ] underwent intraoperative AAA-sac embolization as reported in a previous paper [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…11,12,17 Moreover, some reports have suggested that sac embolization during EVAR reduces ELII. 18,19 However, there is currently no strong evidence identifying which patients will benefit the most from preventive branch embolization to avoid ELII. 20 Target and routine embolization of side branches would be unnecessary and time consuming, considering the incidence of ELII and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…These groups have then looked at pre-emptive coil embolization to prevent T2Es. [2][3][4] Clearly, if we can decrease the need for secondary procedures in EVAR patients, that would be beneficial. The question becomes the cost-benefit ratio.…”
Section: Invited Commentarymentioning
confidence: 99%